A biochemical analysis of the interaction of Porphyromonas gingivalis HU PG0121 protein with DNA. - Natalia O Tjokro; Christopher J Rocco; Richa Priyadarshini; Mary E Davey; Steven D Goodman (PLoS ONE)
K-antigen capsule, a key virulence determinant of the oral pathogen Porphyromonas gingivalis, is synthesized by proteins encoded in a series of genes transcribed as a large polycistronic message. Previously, we identified a 77-base pair inverted repeat region with the potential to form a large stem-loop structure at the 5' end of this locus. PG0121, one of two genes flanking the capsule operon, was found to be co-transcribed with the operon and to share high similarity to the DNA binding protein HU from Escherichia coli. A null mutation in PG0121 results in down-regulation of transcription of the capsule synthesis genes and production of capsule. Furthermore, we have also shown that PG0121 gene can complement multiple deficiencies in a strain of E. coli that is deficient for both the alpha and beta subunits of HU. Here, we examined the biochemical properties of the interaction of PG0121 to DNA with the emphasis on the kinds of nucleic acid architectures that may be encountered at the 77-bp inverted repeat. We have concluded that although some DNA binding characteristics are shared with E. coli HU, HU PG0121 also shows some distinct characteristics that set it apart from other HU-like proteins tested to date. We discuss our results in the context of how PG0121 may affect the regulation of the K-antigen capsule expression.